2011
DOI: 10.1027/1864-9335/a000067
|View full text |Cite
|
Sign up to set email alerts
|

What Do Drawings Reveal About People’s Attitudes Toward Countries and Their Citizens?

Abstract: Participants (N = 567) from six countries (Belgium, Ivory Coast, Italy, Kosovo, Portugal, and Switzerland) drew borders of their own and of neighbor countries on boundary-free maps. It was predicted and found that the tendency to overestimate versus underestimate the sizes of the countries, compared to the original maps, reflects the perceiver’s attitudes toward the target country, status asymmetries, and the quality of relations between the ingroup and outgroup countries. The findings are discussed with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In contrast, Edmontonians had roughly three or four regions from west to east, and they were not spaced as far apart. We do not want to make much of this finding at this point, because we did not measure attitudes toward "others," which have previously been shown to play a role specifically in distance estimates (Carbon & Leder, 2005) and map drawing (Lorenzi-Cioldi et al, 2011). However, such a systematic difference in students' mental geographies cannot be ignored in the investigation of any kind of visual neglect or geographical location estimates, because with real-world knowledge (as opposed to line bisection), factors other than perceptual ones may come into play in what is "seen" or not "seen."…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Edmontonians had roughly three or four regions from west to east, and they were not spaced as far apart. We do not want to make much of this finding at this point, because we did not measure attitudes toward "others," which have previously been shown to play a role specifically in distance estimates (Carbon & Leder, 2005) and map drawing (Lorenzi-Cioldi et al, 2011). However, such a systematic difference in students' mental geographies cannot be ignored in the investigation of any kind of visual neglect or geographical location estimates, because with real-world knowledge (as opposed to line bisection), factors other than perceptual ones may come into play in what is "seen" or not "seen."…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, Lorenzi-Cioldi, Buschini, Baerlocher, and Gross (2010) content analyzed a large sample of job offers from daily newspapers and showed that the size of the job offer and the amount of individuating information provided about the occupation and the prospective applicant increased as a function of the job's prestige. Even the size of a nation is largely overestimated in blank maps according to the target nation's perceived status and wealth (Lorenzi-Cioldi et al, 2011).…”
Section: A Status-individualization Relationshipmentioning
confidence: 99%
“…Wieber and colleagues (Wieber, Gollwitzer, & Seebaß, 2011) did a great job demonstrating the breadth of the field of intention by gathering work on the impact of conscious thought on action control (Epstude & Roese, 2011; McCrea & Hirt, 2011; Unger & Stahlberg, 2011; Wieber, von Suchodoletz, Heikamp, Trommsdorff, & Gollwitzer, 2011), on the impact of conscious thought on automatic action control (Rothermund, 2011; Vogt, De Houwer, & Moors, 2011), on the impact of unconscious processes on action control (Kuhl & Quirin, 2011; Pacherie, 2011), and on the distinction between conscious and unconscious action control (von Suchodoletz & Achtziger, 2011; Schmitz, 2011). Maass and Suitner (2011, p. 161) organized their special issue on spatial constraints on social cognition around three major topics: the role of distance in the interpersonal sphere (Delevoye-Turrell, Vienne, & Coello, 2011; Henderson, Wakslak, Fujita, & Rohrbach, 2011; Matthews, & Matlock, 2011; Steidle, Werth, & Hanke, 2011), spatial metaphors of abstract concepts (Koch, Glawe, & Holt, 2011; Lakens, Semin, & Foroni, 2011; Lorenzi-Cioldi, Chatard, Marques, Selimbegovic, Konan, & Faniko, 2011; Ruscher, 2011), and the processes underlying the relationship between space and social cognition (Kadzandjian, Gaash, Love, Zivotofsky, & Chokron, 2011; Vaid, Rhodes, Tosun, & Eslami, 2011). Many of these contributions to both special issues will likely become widely cited, thus rendering the guest editors’ endeavors great successes.…”
mentioning
confidence: 99%